Early maladaptive schemas in eating disorders: A systematic review. (12th October 2021) - Maher, Anthea; Cason, Liana; Huckstepp, Tyrone; Stallman, Helen; Kannis‐Dymand, Lee; Millear, Prudence; Mason, Jonathan; Wood, Andrew; Allen, Andrew
Abstract: Objective: Research and theory suggest the aetiological nature and symptomatic profile of eating disorders (EDs) can be explained by multiple factors, including the development of early maladaptive schemas (EMS). Yet, there is lack of consensus regarding the evidence supporting the relationship between EMS and EDs. Therefore, this systematic review aimed to examine existing literature concerning the relationship between different ED diagnoses and EMS to provide a synthesis and evaluation of relevant research. Method: A comprehensive literature search of four electronic databases was conducted and studies were included that examined the association between EMS and EDs. Studies were required to use a variant of Young Schema Questionnaire and establish ED diagnosis or symptomology using self‐report questionnaires or clinical interview. Results: A total of 29 studies were included in the review. Compared to healthy controls and varying clinical populations, individuals with EDs generally reported significantly higher scores across all EMS except for Entitlement. Furthermore, Unrelenting Standards consistently appeared as a significant EMS across all ED diagnoses whilst Insufficient Self‐Control was significantly lower in ED diagnoses with restrictive behaviour compared to diagnoses with binge eating or purging behaviour. Discussion: Research supports significant associations between EMS and EDs, which may contribute to our understanding of ED aetiology, including different diagnostic categories. This review underscores the need for studies to explore more gender and age diverse samples and highlights important implications for practitioners. Key points: Individuals with eating disorders reported significantly higher early maladaptive schema (EMS) scores compared to non‐clinical populations Unrelenting standards was noted as a prominent EMS across all eating disorder diagnoses Insufficient self‐control differentiated restrictive versus binge and purging behaviour Although associations between EMSs and eating disorder symptomatology remains putative due to research methodology, the findings provide support for Schema‐focused conceptualisation and intervention